2017
DOI: 10.2134/jeq2016.07.0248
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soluble Phosphorus Loads to Lake Erie: Unintended Consequences of Conservation Practices?

Abstract: Cumulative daily load time series show that the early 2000s marked a step-change increase in riverine soluble reactive phosphorus (SRP) loads entering the Western Lake Erie Basin from three major tributaries: the Maumee, Sandusky, and Raisin Rivers. These elevated SRP loads have been sustained over the last 12 yr. Empirical regression models were used to estimate the contributions from (i) increased runoff from changing weather and precipitation patterns and (ii) increased SRP delivery (the combined effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
206
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(217 citation statements)
references
References 48 publications
7
206
0
4
Order By: Relevance
“…These surveys correspond well to studies examining the ranges in soil test levels across the WLEB. In a study of soil test P (as Mehlich 3) in the Sandusky River Basin, as well as from a database of Ohio soil tests for the WLEB, most soils (70%) were within the "build-up" or "maintenance" ranges for corn and soybean (Baker et al 2017). This implies that only 30% of fields were bad actors, and further analysis suggests that only targeting reductions in this 30% would be insufficient to reach reductions required to reduce algal blooms in Lake Erie.…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
See 3 more Smart Citations
“…These surveys correspond well to studies examining the ranges in soil test levels across the WLEB. In a study of soil test P (as Mehlich 3) in the Sandusky River Basin, as well as from a database of Ohio soil tests for the WLEB, most soils (70%) were within the "build-up" or "maintenance" ranges for corn and soybean (Baker et al 2017). This implies that only 30% of fields were bad actors, and further analysis suggests that only targeting reductions in this 30% would be insufficient to reach reductions required to reduce algal blooms in Lake Erie.…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
“…This implies that only 30% of fields were bad actors, and further analysis suggests that only targeting reductions in this 30% would be insufficient to reach reductions required to reduce algal blooms in Lake Erie. As Baker et al (2017) concluded, "Achieving a 40% reduction in dissolved reactive P loading will require adoption of BMPs in fields across the full range of agronomic soil-test levels. "…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…When conservation practices that are designed to trap sediment are implemented to reduce agricultural phosphorus water quality impacts, nutrients are retained on the landscape. If improperly managed, this accumulated phosphorus can eventually leak out of the system through erosion or desorption from the soil, which results in long-term losses of phosphorus to the stream that are referred to as legacy phosphorus (Jarvie et al, 2017).…”
mentioning
confidence: 99%